2007
DOI: 10.1016/s1808-8694(15)31180-0
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis - an assessment protocol proposal

Abstract: There are important costs involved in halitosis assessment and treatment, including medical appointments, specialist assessment, and complementary tests. Such costs would be minimized by adopting a protocol of evidence-based anamnesis and a flowchart for a rational clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Alcohol ingestion may result in transient halitosis because some substances can cause xerostomia and alcoholic beverages are known to produce volatile compounds, acetaldehyde, and other odorous by-products by oxidation of alcohol in the mouth and liver [ 49 ]. However, similar to previous studies [ 22 , 40 ], participants who consumed alcohol showed no association with self-reported halitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol ingestion may result in transient halitosis because some substances can cause xerostomia and alcoholic beverages are known to produce volatile compounds, acetaldehyde, and other odorous by-products by oxidation of alcohol in the mouth and liver [ 49 ]. However, similar to previous studies [ 22 , 40 ], participants who consumed alcohol showed no association with self-reported halitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that tonsilloliths are clinically related to halitosis and prior history of repeated tonsillitis in childhood and/or tonsillar abscesses. Patients with tonsilloliths have a tenfold increase in the incidence of halitosis [ 20 , 22 24 ]. No treatment is required for most tonsillar calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…One must keep in mind that the patient suffering of halitosis is a person looking for help, often anxious and suspicious of any treatment, due to bad experiences using traditional approaches. [ 42 ] An accurate diagnosis of halitosis must be achieved to manage it effectively. The available methods can be divided into a mechanical reduction of microorganisms, chemical reduction of microorganisms, usage of masking products, and chemical neutralization of VSC.…”
Section: How Is Halitosis Managed?mentioning
confidence: 99%